2007
DOI: 10.1137/060672522
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic Profiles of the Steady States for an SIS Epidemic Patch Model

Abstract: Spatial heterogeneity, habitat connectivity, and rates of movement can have large impacts on the persistence and extinction of infectious diseases. These factors are shown to determine the asymptotic profile of the steady states in a frequency-dependent SIS (susceptible-infectedsusceptible) epidemic model with n patches in which susceptible and infected individuals can both move between patches. Patch differences in local disease transmission and recovery rates characterize whether patches are low-risk or high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
258
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 208 publications
(268 citation statements)
references
References 25 publications
8
258
2
Order By: Relevance
“…Allen et al [2] studied a frequency-dependent SIS metapopulation model, which in our notation is given by…”
Section: Discussionmentioning
confidence: 99%
“…Allen et al [2] studied a frequency-dependent SIS metapopulation model, which in our notation is given by…”
Section: Discussionmentioning
confidence: 99%
“…They showed that, while the population is at an endemic level, increased travel rates of infectives can cause disease extinction in all patches. In a similar setting, Allen et al [3] showed for a frequency-dependent SIS deterministic model that, while the population is at an endemic level and if infectious individuals travel between the patches but the rate of travel for susceptible individuals approaches 0, then, contrary to what is expected, the endemic equilibrium approaches a disease-free equilibrium. McCormack and Allen [141] studied an SIR and an SIS model in both deterministic and stochastic settings, assuming disease independent travel rates.…”
Section: Accounting For Mobilitymentioning
confidence: 96%
“…The major drawback of these models is the absence of mobility, in both deterministic and stochastic settings. This is overcome for deterministic models in the studies made by Bailey [15,Section 7.33], Hethcote [98], Sattenspeil and Dietz [187], Allen et al [3], McCormack and Allen [141], van den Driessche [202], Salmani and van den Driessche [183], Arino and van den Driessche [9,10,11], Arino et al [7,8], Wang and Zhao [210], Wang and Mulone [209], Jin and Wang [107], Kuniya and Muroya [124], and Muroya et al [145]. The authors who have contributed on the stochastic side include Ball [22], Ball and Clancy [24,25], Clancy [50,52], Keeling et al [112,114], Sani et al [185], Lahodny Jr and Allen [131] and Neal [152].…”
Section: Accounting For Mobilitymentioning
confidence: 99%
See 2 more Smart Citations